Adoption of cloud computing in business continuity management for container terminal operations in South Africa. (26th July 2022) - Ochara, Nixon Muganda; Kutame, Felix Nyadzani; Kadyamatimba, Armstrong
This study responds to recent calls for improving pre- and post-disaster business continuity by investigating cloud computing adoption factors relevant to the modernisation of port operations. A fit-viability model (FVM) is used as the analytical framework for the study. An interpretive, qualitative methodology, employing the use of a case study of the ports in South Africa was adopted. The interview data collected was analysed thematically and the findings revealed several insights: the first is that a digitalised BCM architecture 'fits' the cloud computing model. Secondly, the cloud computing model is a 'viable' model that can contribute to managing complex and differentiated organisations. For such complex organisations, viability can be realised by harnessing collective intelligence (CI) for more effective BCM. Lastly, to realise digitally enabled BCM and harness the power of CI, there is need for a rethinking of strategy towards the adoption of an 'intelliport strategy' or 'smart' BCM for ports.